Chemical Warfare Operations - Malik M.A. Fakron (Chemical Warfare and Environmental Warfare Operations, Edition 1, 2025)
In 1915, the first Chemical warfare operation in modern history happened. The development of chemical warfare agents was done based on experimental chemistry and the animal science laboratory for testing and measurement of toxicity dose and lethal dose. The aim of this chapter is to provide a stable foundation for the design of chemical warfare agents and design principles for chemical warfare operations, based on theoretical physical chemistry, fluid flow mechanics and theoretical thermodynamics. Optimum gas chemical warfare agents have the following characteristics: colorless, odorless and lethal concentrations at very low concentrations. Very low hydrolysis in water, high stability and high solubility in water. There are several stages for the development of any chemical warfare agent; the focal stages are the selection of the method of exposure and the harm mechanisms. The main elements and groups used for the development of gas-chemical warfare agents are classified based on their harm mechanisms. The first group of halogens is Cl, F, Br, and I. The second group is unsaturated oxides: carbon monoxide and sulfur oxides. The third group is toxic elements such as cyanide, sulfur, and arsenic. The Fourth group is organic phosphorus. These elements and groups are combined with Phenyl, Benzyl, Xylyl, Methyl, Ethyl, and Vinyl groups such as Halogens Methyl. There are several kinds of calculations and experimental testing to be carried out, such as thermodynamics calculations, reaction kinetics, reaction rates for any chemical agents with target compounds, and then experimental studies for the effect of gas agents on animals. Design chemical warfare operation has many process parameters to study, for developing the desired chemical cloud for the volume occupying three meters above ground for the battlefield area. Meteorological parameters are very important for atmospheric fluid flow in the design of chemical warfare operations. Chemical warfare gas agents at lethal requirement concentration produce the highest lethality rate. This is a combined process of convective mass transfer and diffusion mass transfer. For Producing chemical cloud with lethal concentration at a time of operations, with respect meteorological parameters.